Convergence Culture Reconsidered Media - Participation - Environments - Georgi, Claudia; Glaser, Brigitte Johanna (Universitätsverlag Göttingen, 2015)
Taking media scholar Henry Jenkins's concept of 'convergence culture' and the related notions of 'participatory culture' and 'transmedia storytelling' as points of departure, the essays compiled in the present volume provide terminological clarification, offer exemplary case studies, and discuss the broader implications of such developments for the humanities. Most of the contributions were originally presented at the transatlantic conference Convergence Culture Reconsidered organized by the editors at the Georg-August-Universität Göttingen, Germany, in October 2013. Applying perspectives as diverse as literary, cultural, and media studies, digital humanities, translation studies, art history, musicology, and ecology, they assemble a stimulating wealth of interdisciplinary and innovative approaches that will appeal to students as well as experts in any of these research areas.